Navigating Liquidity Constraints: Assessing Bank Resilience to Deposit Volatility during Contractionary Monetary Policy Phases - Wursan (CV. HEI PUBLISHING INDONESIA, 2026)
This study examines the effects of Deposit Volatility (DVOL), the BI Rate, Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Firm Size on bank liquidity, proxied by the Banking Ratio Loan-to-Deposit Ratio (BR_LDR), in Indonesian state-owned banks (HIMBARA) listed on the Indonesia Stock Exchange during 2021–2024. A quantitative approach was employed using secondary data collected from the annual reports of PT Bank Rakyat Indonesia (Persero) Tbk, PT Bank Mandiri (Persero) Tbk, PT Bank Negara Indonesia (Persero) Tbk, and PT Bank Tabungan Negara (Persero) Tbk. Panel data regression analysis was conducted using EViews, with the Fixed Effect Model (FEM) selected based on the Chow test. The results indicate that the BI Rate and Firm Size significantly influence BR_LDR at the 10% significance level, whereas Deposit Volatility, CAR, and NPL have no significant effect. The F-test shows that the independent variables jointly have a significant effect on BR_LDR. The coefficient of determination (R²) of 35.2% indicates that the model moderately explains variations in bank liquidity, while the remaining variation is attributable to other internal and external factors. These findings provide insights for banks in strengthening liquidity management and offer a reference for future studies on banking liquidity.